Rotation of the 10 keV Electron Beam By 360° Using PVC Tubes - Myshelovka, L. V.; Piatigor, A. D.; Vokhmyanina, K. A.; Sotnikova, V. S.; Kubankina, A. A.; Grigoriev, Yu. V.
We measured the time dependence of the passage of an electron beam with an energy of 10 keV and a beam current of about 1.8 μA through PVC tubes bent into rings by 360°. The tubes with the following parameters were used: one with the inner diameter of the tube 2.8 mm, the diameter of the ring 75 mm; and another with an inner diameter of 4 mm, and a ring diameter of 150 mm. In both cases, the current of transmitted electrons was about 15% of the incident current. Measurement of the electron spectrum for a ring of smaller diameter showed that all electrons that passed through it lose their initial energy.
Keywords: Physics